The Agri-Food Systems Transformation Protocol - Mapping Agents and Drivers of Transformation - Shah, Tavseef Mairaj; Riemer, Olivia; El Hage Scialabba, Nadia; Müller, Alexander; Caron, Patrick; MeFleckenstein, Martina; Hilmi, Angela; Hoffmann, Ulrich; Kimani-Murage, Elizabeth; Mulet, Michael; Kollenda, Elisa; Plötz, Tanja; et al. (Think Tank for Sustainability, 2023)
The Agri-food Systems Transformation Protocol proposed in this report provides a concise guide to developing transformation pathways in different contexts and at different levels. It ix FORESEE SERIESis designed to help a wide variety of decision-makers, stakeholders and actors – including agri-food producers and businesses, grassroots groups, practitioners, researchers, national policymakers, and international organizations – gain a clearer understanding of what must be done and in which sequence. The protocol is intended as a first step in developing a theory of transformative change for agri-food systems. Use of the protocol is, on its own, no guarantee for successful transformation. Many pitfalls must be cautiously negotiated, including the challenges of administrative change and dealing with private interests and political will. The protocol is not a magic bullet but it has the potential to provide structure and coordination for the complex endeavour of transforming agri-food systems.